Arrhythmogenic syncope leading to cardiac rhythm management procedures during COVID-19 lockdown. (1st November 2020) - Russo, Vincenzo; Pafundi, Pia Clara; Rapacciuolo, Antonio; D'Andrea, Antonello; de Devitiis, Marcello; Volpicelli, Mario; Ruocco, Antonio; Nigro, Gerardo; D'Onofrio, Antonio
ABSTRACT: Introduction : Following the coronavirus disease (COVID-19) outbreak, the Italian government adopted strict rules of lockdown and social distancing. The aim of our study was to assess admission rate for syncope leading to cardiac rhythm management (CRM) procedures in Campania, the third-most-populous region of Italy, during COVID-19 lockdown. Methods : Data were sourced from 14 referral hospitals in Campania from 10 th March to 4 May 2020 (lockdown period) and during the same period in 2019. Among consecutive patients hospitalized for CRM procedures during the two observational periods, we retrospectively evaluated those admitted for arrhythmogenic syncope. Admission rate and the type of hospital admission between the two observational periods were compared. Results : Among 951 consecutive patients hospitalized for CRM procedures, 204 were admitted for arrhythmogenic syncope leading to CRM procedures. A significant increase in admission was shown in 2020 compared to 2019 (26.4% vs. 18.3%; P = 0.003 ). Moreover, regarding the type of admission to hospitals, attendance at the emergency department (ED) significantly increased (83.5% vs. 56.1%; P < 0.001 ); conversely, a significant decrease in urgent unplanned hospitalizations (6.2% vs. 35.5%; P < 0.001 ) was observed during COVID-19 lockdown. Conclusions : The hospitalization for arrhythmogenic syncope leading to CRM procedures increased during COVID-19 lockdown.